KARAKTERISTIK SOSIS BERBAHAN BAKU CAMPURAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) DAN OTAK SAPI - Fiola Hamanda Prisilia; Yhulia Praptinngsih; Rizka Rian Fauziah (Faculty of Agricultural Technology, University of Jember, 2017)
sage is a processed product which have meat as its main ingredients and the extender ingredients are binders, filler, sugar, salt and also seasoning then mixed and put it into a casing. Commonly sausage use meat as its raw ingredient.The expensive price of meat will cause the price of sausage also increasing, so then an innovation to use another main ingredients as the alternative of meat that is cheaper, such as white oyster mushroom. Oyster mushroom have protein and fiber but also contain low level of fat, so it need to increase of fat content by cow’s brain. Cow’s brain have high of fat content so that it will be useful to increase the fat content in the oyster mushroom mixed with cow brain sausage. The purpose of this experiment is to find the right ratio in the process of mixing white oyster mushroom with cow brain. This experiment was conducted by the Complete Randomized Design. The treatment was ratio of oyster mushroom and cow brain it had 5 levels. The oyster mushroom and cow brain ratio are P1 (90:10); P2 (80:20); P3 (70:30); P4 (60:40); P5(50:50). The parameter of the observation are texture, colour, cooking loss,apperance of the slice, moisture content, fat content, and sensoric properties was the preference of colour, flavour, texture, taste and overall. The best treatment was analysis of proximate test. Based on effectiveness test from this research, the best formulation was on P5 treatment (oyster mushroom and cow meat ratio 50:50). The sausage had score of texture of 63 g/1,5mm; color 57,59; cooking loss 7,11%; moisture content 60,31%; fat content 4,22%; protein content 21,05%; ash content 2,08%; carbohydrate content 12,34%; preference of colour, smell, texture, taste and overall was 5,7;6,36;5,36;5,75;5,92 (neutral- a bit of contentment). Keywords: sausage, oyster mushrooms, cow’s brain, ratio